Impact of milk feeding frequency on performance, health and behaviour of crossbred cattle calves - HAJAM, JAVID REHMAN; GAUR, G K; DUTTA, NARAYAN; BHARTI, P K; SINGH, MUKESH; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to study the impact of milk feeding frequency on performance, health and behaviour of crossbred cattle calves. A total of 12 crossbred (Vrindavani) calves were allocated equally in to two groups viz. control (G-I) and experimental group (G-II). During the experimental period (from16th to 70th day of birth), the calves in Gr-II and G-I group were fed milk once and twice daily, respectively without any change in total offered milk quantity. The mean birth weight (kg) of calves in control and experimental group were 21.01±0.88 and 21.25±0.88 kg, respectively. The total body weight gain of calves in control and experimental group were 21.06±0.39 and 21.08±0.39 kg, respectively. The average weekly body weights, gains and body measurements in general were non-significantly different in control and G-II group from 1st to 10th week of age. However, the body length was significantly (P